2019
DOI: 10.1029/2019gl082278
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of Gigantic Jets From Geostationary Orbit

Abstract: Here we report the first observations of gigantic jets (GJs) by the Geostationary Lightning Mapper (GLM) on board the Geostationary Operational Environmental Satellite‐R series. Fourteen GJs produced by Tropical Storm Harvey on 19 August 2017 were observed by both GLM and a ground‐based low‐light‐level camera system. The majority of the GJs produced distinguishable signatures in the GLM data, which include long continuous emissions, large peak flash optical energies, and small lateral propagation distances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 28 publications
9
29
0
Order By: Relevance
“…Figure 6 shows the evolution of the brightest GLM pixel. Similar to Boggs et al 34 , we find that two adjacent pixels (about 14 × 7 km), the brightest one corresponding to the GJ azimuth, are consistently brighter than surrounding ones.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 6 shows the evolution of the brightest GLM pixel. Similar to Boggs et al 34 , we find that two adjacent pixels (about 14 × 7 km), the brightest one corresponding to the GJ azimuth, are consistently brighter than surrounding ones.…”
Section: Resultssupporting
confidence: 91%
“…Their supplementary images 12 remarkably show how the lowest sections of two separate jet branches (frame 9) later fused into one bright stem (frame 12 and after). Similar persistent bright stems can be found between 18 and 26 km in the video images of close range recent jet events 16,18,24,34 resembling cloud-to-air lightning branches and their streamer coronas 35 . This stem flickers simultaneously with the cloud lightning flash, and often reappears brightest at the end of the event 11,12,1618,36 .…”
Section: Introductionsupporting
confidence: 70%
“…Journal of Geophysical Research: Atmospheres (Figure 4e). The GJ location was marked by cyan "×" in Figure 5a and was located in the area of the lowest cloud top brightness temperature with −64°C, which was consistent with the previous results (Boggs et al, 2019;Singh et al, 2017;Soula et al, 2011).…”
Section: 1029/2019jd031538supporting
confidence: 90%
“…The GJ established a direct path of an electrical connection between the cloud top and the ionosphere (Cummer et al, 2009;Kuo et al, 2009), which has an important influence on the electron density and potential of the ionosphere, electromagnetic environment of the near space, and radio communication. Since the first GJ was observed on 14 September 2001 by Pasko et al (2002) in Puerto Rico, several GJs have been observed by ground-based (Cummer et al, 2009;He et al, 2019;Lu et al, 2011;Peng et al, 2018;Soula et al, 2011;Su et al, 2003;Van der Velde et al, 2007 and satellite-based experiments (Boggs et al, 2019;Chen et al, 2008;Kuo et al, 2009). Optical observations show that most of the observed GJs have "tree" or "carrot" shape (Liu et al, 2015;Pasko et al, 2002;Soula et al, 2011;Su et al, 2003) and there is a color transition zone between the two areas where the bottom (altitude 20-40 km) is blue and the top (altitude over 65 km) is red (Peng et al, 2018;Soula et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some lightning phenomena can generate optical emissions that persist over multiple frames. Examples include continuing currents (Bitzer, 2017), gigantic jets (Boggs et al, 2019), and K process waves in horizontally expansive lightning channels (Winn et al, 2011).…”
Section: Optical Lightning Flash Clustering Algorithmmentioning
confidence: 99%